Edukasi Hipertensi Dan Manajemen Nyeri Dengan Teknik Distraksi Menggunakan Media Audiovisual Untuk Meningkatkan Pengetahuan Pada Penderita Hipertensi - Zaky Ariyanto, Hafizh; Susanto, Amin; Wirakhmi, Ikit Netra (Yayasan Inspirasi El Burhani, 2024)
Introduction: Hypertension in the elderly is very important to know because the pathogenesis, course of the disease and its management are not entirely the same as hypertension in adults of easy age. Pain is subjective, while the discomfort experienced by a person can be known from autoanamnesis. Distraction technique is a way to relieve pain by diverting the patient's attention to other things so that the patient will forget about the pain he feels. Objective: This service aims to help increase the knowledge of hypertensive elderly people in managing pain against hypertension at the RW/5 Ledug elderly Posyandu. Method: The method of community service activities is to conduct Hypertension Counseling and Pain Management with Distraction Techniques Using Audiovisual Media to Increase Knowledge of Hypertension Patients. This community service activity begins with giving a post-test in the form of a questionnaire to measure the level of knowledge before being given education, then participants are given education, and after participants are given education, a questionnaire is given again to measure the level of knowledge after being given education. Result: The results of community education activities showed that the knowledge value of participants before education was in the good category as many as 23 respondents (76.7%), the moderate category was 7 respondents (23.3%). participants after education in the good category were 30 respondents (100%), the moderate category was 0 respondents (0%). Conclusion: From the results of the service it can be concluded that there is an increase in knowledge in people with hypertension.